Recycling of non-metallic automotive shredder residues and coal fly-ash in cold-bonded aggregates for sustainable concrete. (1st May 2017) - Colangelo, F.; Messina, F.; Di Palma, L.; Cioffi, R.
Abstract: In order to achieve the relevant objectives of EC directive on end-of-life of vehicles (2000/53/CE), innovative solutions such as recycling automotive shredder residues are required. This paper deals with the design and characterization of concrete mixtures containing artificial aggregates obtained through the cold-bonding pelletization of non-metallic fraction of automotive shredder residues, commonly named car fluff. In this work, car fluff was pelletized with blended cementitious mixtures containing coal fly ash, another industrial by-product. Produced artificial aggregates were characterized by determining main environmental, physical and mechanical properties. Then, they were employed as lightweight aggregates for manufacture of sustainable concrete. Experimental results showed good mechanical properties of concrete containing these aggregates and leaching behaviour of hardened specimens confirmed the environmental effectiveness of the here studied car fluff recovery process. Highlights: Recycling of non-metallic automotive shredder residues is promoted by EC directive 2000/53. Pilot scale cold-bonding pelletization is performed to recycle both automotive shredder residues and coal fly ash. Physical, mechanical and environmental characterization of artificial aggregates shows process feasibility. Concrete specimens made with recycled aggregates exhibits satisfactory physico-mechanical properties.